The persistence and conservation of Borneo's mammals in lowland rain forests managed for timber: observations, overviews and opportunities - Meijaard, E.; Sheil, Douglas (2008)
Lowland rainforests on Borneo are being degraded and lost at an alarming rate. Studies on mammals report species responding in various ways to habitat changes that occur in commercial forestry concessions. Here we draw together information on the relationship between the ecological, evolutionary, and biogeographic characteristics of selected Bornean nonvolant mammals, and their response to timber harvesting and related impacts. Only a minority of species show markedly reduced densities after timber harvesting. Nonetheless there are many grounds for concern as various processes can, and often do, reduce the viability of wildlife populations. Our review of what we know, and of current understanding, helps predict mammalian dynamics and subsequent mammal-induced ecosystem changes in logged forests. We identify groups of mammal species that, although largely unstudied, are unlikely to tolerate the impacts associated with timber harvesting. On a positive note we find and suggest many relatively simple and low-cost ways in which concession management practices might be modified so as to improve the value of managed forests for wildlife conservation. Improving forest management can play a vital role in maintaining the rich biodiversity of Borneo’s tropical rain forests.